High Incidence of Cranial Synostosis and Chiari I Malformation in Children With X‐Linked Hypophosphatemic Rickets (XLHR). (20th November 2018) - Rothenbuhler, Anya; Fadel, Nathalie; Debza, Yahya; Bacchetta, Justine; Diallo, Mamadou Tidiane; Adamsbaum, Catherine; Linglart, Agnès; Di Rocco, Federico
ABSTRACT: X‐linked hypophosphatemic rickets (XLHR) represents the most common form of genetic hypophosphatemia and causes rickets and osteomalacia in children because of increased FGF23 secretion and renal phosphate wasting. Even though cranial vault and craniovertebral anomalies of potential neurosurgical interest, namely early closure of the cranial sutures and Chiari type I malformation, have been observed in children with XLHR, their actual incidence and characteristics are not established. The aims of this study were to analyze the incidence of cranial and cervico‐occipital junction (COJ) anomalies in children with XLHR and describe its features. This is a retrospective study of CT scans of the head and skull in 44 XLHR children followed at the French Reference Center for Rare Diseases of the Calcium and Phosphate Metabolism. Forty‐four children with XLHR, 15 boys and 29 girls, aged 8.7 ± 3.9 years at time of CT scan, were studied. We found that 59% of XLHR children had a complete or partial fusion of the sagittal suture and 25% of XLHR children showed protrusion of the cerebellar tonsils. A history of dental abscesses was associated with craniosynostosis, and craniosynostosis was associated with abnormal descent of cerebellar tonsils. Only 2 patients showed neurologic symptoms. Four of 44 patients (9%) required neurosurgery. This study highlights that sagittal suture fusion and Chiari type I malformation are frequent complications of XLHR. The incidence of sagittal synostosis in XLHR is actually extremely high and was probably underestimated so far. Chiari type I malformation is also frequent. Because diagnosis of craniovertebral anomalies can be underestimated on a purely clinical basis, radiological studies should be considered in XLHR children if a proper diagnosis is warranted. © 2018 The Authors. Journal of Bone and Mineral Research Published by Wiley Periodicals, Inc.